1999
DOI: 10.1111/j.1348-0421.1999.tb01231.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Cell Wall Composition Leads to Amphotericin B Resistance in Aspergillus flavus

Abstract: An amphotericin B (AmB)‐resistant mutant was isolated from a wild‐type AmB‐susceptible strain of Aspergillus flavus by serial transfer of conidia on agar plates containing stepwise increased concentrations of AmB up to 100 μtg ml−1. The acquired resistance of my celia was specific for polyene‐antibiotics AmB, nystatin and trichomycin. Spheroplasts derived from the resistant mycelia were as susceptible to AmB as the wild‐type. Chemical analysis of the cell wall revealed that levels of alkali‐soluble and ‐insolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 46 publications
(24 reference statements)
1
46
0
2
Order By: Relevance
“…Ergosterol levels are reported to be the main cause for resistance to this drug, with both increased as well as decreased levels of ergosterol being correlated with amphotericin B sensitivity (Pasrija et al, 2005;Sanglard et al, 2003). In many reports of fungal resistance to this drug, there have also been increases in chitin or glucan levels (Bahmed et al, 2002;Seo et al, 1999). However, in Candida there is at least one report that correlates amphotericin B resistance with decreased chitin levels (Bahmed et al, 2003).…”
Section: Discussionmentioning
confidence: 93%
“…Ergosterol levels are reported to be the main cause for resistance to this drug, with both increased as well as decreased levels of ergosterol being correlated with amphotericin B sensitivity (Pasrija et al, 2005;Sanglard et al, 2003). In many reports of fungal resistance to this drug, there have also been increases in chitin or glucan levels (Bahmed et al, 2002;Seo et al, 1999). However, in Candida there is at least one report that correlates amphotericin B resistance with decreased chitin levels (Bahmed et al, 2003).…”
Section: Discussionmentioning
confidence: 93%
“…Although the true rate of AmB resistance is unknown, some investigators have reported isolates of A. flavus resistant to AmB in vitro (Odds et al, 1998;Lass-Florl et al, 1998;Seo et al, 1999;Mosquera et al, 2001;Gomez-Lopez et al, 2003;Sutton et al, 2004;Hsueh et al, 2005), although this is not universally accepted. In a study from Taiwan (Hsueh et al, 2005) isolates of A. flavus and A. fumigatus with reduced susceptibilities to AmB were found (MICs 2 mg ml 21 ).…”
Section: Amphotericin Bmentioning
confidence: 99%
“…Rapid identification of molds causing invasive disease could facilitate the timely administration of effective therapy. For example, Aspergillus flavus and Aspergillus terreus have been reported to be resistant to amphotericin B (39,45), and Aspergillus fumigatus can become resistant to itraconazole (9).…”
mentioning
confidence: 99%